Diversity of lichen in UiTM Negeri Sembilan Forest / Noor Hazlina Jamaluddin - Jamaluddin, Noor Hazlina (2016)
Lichen is an organism made up of mutualism interaction between algae and fungus. Studies regarding lichen in Malaysia is still at the beginning stage and there were very few studies had been conducted with regard to its diversity in Malaysia. A preliminary study on the diversity of lichen in UiTM Negeri Sembilan Forest was conducted. Lichen samples were collected from three different areas within UiTM Negeri Sembilan forest and went through the preservation and identification process in the laboratory. The identification process were carried out based on physical observation and chemical test in which the colour spot test was conducted. A total of 19 species of lichens have been identified which made up of 7 families and 9 genera. From all the species found, 17 of them were crustose lichen and another 2 were foliose lichen. The genus were mainly from Steroecaulaceae major division namely Lepraria. Advance research can be conducted in order to discover the benefits of this lichen.